The Effect of Self-Help Group (SHG) on Family's Ability in Treating Person with Mental Illness (PWMI) - Enggal Hadi Kurniyawan; Erti Ikhtiarini Dewi; Emi Wuri Wuryaningsih; Fitrio Deviantony; Yeni Fitria (Nursing and Health Sciences Journal (NHSJ), 2023)
The community health center in Jember Regency has not been optimal in overcoming mental disorders in the community, causing increasingly complex mental health problems and impacting not only individuals but families and society itself. The family approach using self-help group (SHG) therapy is one way to be able to provide treatment for Person With Mental Illness (PWMI). The role of mental nurses is to explore mental health problems in PWMI and psychosocial problems in families with PWMI by giving SHG therapy. This study aimed to analyze the effect of self-help groups on the family's ability to care for PWMI. This study uses a pre-experimental design approach with a one-shot case study method. The measuring instruments used were self-help group SOP, PWMI daily living activity observation sheets, and a questionnaire on the family's ability to care for PWMI. The SHG will be held for four sessions involving PWMI, families, and the person in charge of mental health programs at the community health center. The results showed a significant increase in the family's cognitive abilities before and after getting a self-help group with a P-value of 0.040. and a significant increase in psychomotor abilities with a P-value of 0.043. It is hoped that nurses can form SHG to improve PWMI care in the community